The Wits Of Mother In Dividing Time On Both Managing Family And Writing Blog In Katherine Dieckmann's Motherhood Movie (2009): A Feminist Approach - SARASWATI , RINA (2012)
The object of the study is a movie Motherhood directed by Katherine Dieckmann. The study is to clarify how a mother shows her wits in dividing time reflected in Motherhood directed by Katherine Dieckmann published in 2009. The objective of the study is to analyze the structural elements in the movie and to analyze mother's wits of the movie based on feminist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the eventsof the movie and script of Motherhood and the secondary data source is the article, internet, book, and reference. The method of collecting data is documentation. The technique of analyzing data is descriptive. The results of the study are as follows. First, based on the structural analysis, Katherine Dieckmann delivers a moral message that women must be critical and have wits on dividing time between managing family and writing something in her life. The structural elementsare related to each other and form a unity. Second, based on the feminist analysis, Katherine Dieckmann reflects woman as a mother who is subordinate in the family.